2019
DOI: 10.1016/j.neurobiolaging.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Aging circadian rhythms and cannabinoids

Abstract: Numerous aspects of mammalian physiology exhibit cyclic daily patterns, known as circadian rhythms. However, studies in aged humans and animals indicate that these physiological rhythms are not consistent throughout the life span. The simultaneous development of disrupted circadian rhythms and age-related impairments suggests a shared mechanism which may be amenable to therapeutic intervention. Recently, the endocannabinoid system has emerged as a complex signaling network which regulates numerous aspects of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 192 publications
0
23
0
1
Order By: Relevance
“…The relation between the circadian system and aging has long been acknowledged, however the direction of this relationship remains elusive 7 . What is generally accepted, is that aging affects the entrainment of the central clock in various ways, and that dyssynchrony in the central clock can cause dysregulations in the peripheral clocks 32 . What is still under debate, however, is if peripheral clocks are individually affected upon aging, given that many age-induced effects appear to be tissue-specific 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The relation between the circadian system and aging has long been acknowledged, however the direction of this relationship remains elusive 7 . What is generally accepted, is that aging affects the entrainment of the central clock in various ways, and that dyssynchrony in the central clock can cause dysregulations in the peripheral clocks 32 . What is still under debate, however, is if peripheral clocks are individually affected upon aging, given that many age-induced effects appear to be tissue-specific 30 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that cannabis may act centrally as a zeitgeber (Whitehurst et al, 2015 ), entraining biological rhythms to facilitate daily sleep periods, and thus may serve as a chronobiotic therapeutic compound for individuals with disrupted circadian function, such as the elderly (Hodges and Ashpole, 2019 ). Evidence suggests there is also chronobiological activity in the eCB system itself in humans.…”
Section: Sleep Studies In Humansmentioning
confidence: 99%
“…For example, perinatal exposure to chemicals like dieldrin increased the risk of Parkinson's disease (Richardson et al 2006), while lead is linked to amyloid precursor protein dysfunction and Alzheimer's disease (Reviewed in: Zawia and Basha 2005). In contrast, preconditioning biological systems during critical developmental periods may bolster resilience to age-related dysfunction (Calabrese and Mattson 2017;Gidday 2015;Hodges and Ashpole 2019). Dietary restriction due to litter crowding in early life leads to increased life span (Sun et al 2009).…”
Section: Introductionmentioning
confidence: 99%